Modelling of batch and fed-batch ethanol fermentation - Glyn, Julian E H (Department of Chemical Engineering, 2016)
Two series of batch and fed-batch fermentations were carried out using S.cerevisiae in a semi-defined medium containing 200 gl-1 glucose as limiting substrate. Growth rates were calculated and the data used to test the applicability of eight empirical kinetic models. The form proposed by Levenspiel, combining the concept of a limiting ethanol concentration with a power-law form, gave the best results with these data. Glucose concentration was found to have a far smaller, though not negligible, effect on growth rate under these conditions. It was also observed that in fed-batch fermentations the total substrate uptake rate of the broth became constant soon after commencement of feeding, without cessation of growth. It is suggested that ethanol inhibits the synthesis of a rate-controlling enzyme in the glycolyti·c chain, but no previous work could be found to support or refute this explanation. A quasi-mechanistic model of growth under the condition of constant substrate consumption rate is formulated and discussed.